Fractura de columna cervical con extensa artrodesis previa Tratamiento mediante triple corporectomía más artrodesis circunferencial. [Cervical spine fractures with previous extensive arthrodesis Treatment by triple vertebral body removal plus circumferential arthrodesis]. - Flores Kanter, Diego Nicolas; Ortiz, Pablo Nicolas; Gonzales, Gustavo (Revista de la Asociación Argentina de Ortopedia y Traumatología, 2016)
Fractura de columna cervical con extensa artrodesis previa Tratamiento mediante triple corporectomía más artrodesis circunferencial